Combined rotational atherectomy and cutting balloon angioplasty prior to drug‐eluting stent implantation in severely calcified coronary lesions: The PREPARE‐CALC‐COMBO study. Issue 6 (19th October 2022) - Allali, Abdelhakim; Toelg, Ralph; Abdel‐Wahab, Mohamed; Hemetsberger, Rayyan; Kastrati, Adnan; Mankerious, Nader; Traboulsi, Hussein; Elbasha, Karim; Rheude, Tobias; Landt, Martin; Geist, Volker; Richardt, Gert
Abstract: Objectives: To evaluate the safety and efficacy of lesion preparation using rotational atherectomy (RA) with consecutive cutting balloon angioplasty (Rota‐Cut). Background: Whether the Rota‐Cut combination improves stent performance in severely calcified coronary lesions is unknown. Methods: PREPARE‐CALC‐COMBO is a single‐arm prospective trial in which 110 patients were treated with a Rota‐Cut strategy before implantation of sirolimus‐eluting stents and compared with patients treated with modified balloon (MB, scoring or cutting) or RA from a historical cohort (the randomized PREPARE‐CALC trial). The study had two primary endpoints: in‐stent acute lumen gain (ALG) by quantitative angiographic analysis and stent expansion (SE) on optical coherence tomography. Results: In‐stent ALG was significantly higher with Rota‐Cut compared to RA or MB alone (1.92 ± 0.45 mm vs. 1.74 ± 0.45 mm with MB vs. 1.70 ± 0.42 mm with RA; p  = 0.001 and p  < 0.001, respectively). SE was comparable between groups (75.1 ± 13.8% vs. 73.5 ± 13.3 with MB vs. 73.1 ± 12.2 with RA; p  = 0.19 and p  = 0.39, respectively). The Rota‐Cut combination resulted in higher minimal stent area (MSA) (7.1 ± 2.2mm 2 vs. 6.1 ± 1.7mm 2  with MB vs. 6.2 ± 1.9mm 2 with RA; p  = 0.003 and p  = 0.004, respectively). In‐hospital death occurred in one patient. Target vessel failure at 9 months was low and comparable between groups (8.2% vs. 8% with MB vs. 6% with RA; p  = 1 and p  = 0.79, respectively). Conclusion: Rota‐Cut combination resulted in higher ALG and larger MSA compared with historical control of RA or MB alone, but was not associated with higher SE. Despite extensive lesion preparation, this strategy is safe, feasible, and associated with favorable clinical outcome at 9 months.